ANIMALS AT NIGHT - Flint, Katy; Li, Cornelia (London : Wide Eyed Editions, 2019)
Learn about nocturnal animals in this glow-in-the-dark adventure. Meet the animals that come out at night in this glow-in-the-dark adventure. See the jaguar in the Amazon rainforest, spot the lions on the African savannah and visit a turtle nesting beach under the stars! Then, fold out your incredible glow-in-the-dark poster to stick up on your wall. Simply turn off the light to bring the incredible glow-in-the-dark ink to life.
Keywords: Nocturnal animals -- Juvenile fiction